Thermomechanical process route to achieve high fracture toughness in Ti-17 forgings for high temperature applications - Balzer Mario; Witulski Thomas (MATEC Web of Conferences, 2020)
Mechanical properties of Ti-17 are typically strongly influenced by different thermomechanical process parameters such as applied strain, cooling rates and heat treatment temperatures and times. A variation of theses parameters allows the optimization of material properties. Today Ti-17 is mainly used for aero engine applications, where a high strength and good low cycle fatigue properties are needed up to 450°C. For structural parts damage tolerance properties are the main focus and therefore fracture toughness and fatigue crack propagation are the main driving factors for the design. In large forgings such as aero structural parts, the tempering cross section generally varies significantly, which makes it extremely challenging to achieve uniform properties in each area of the forging especially in case of low buy-to-fly ratio. The aim of this work is to develop a robust thermomechanical processing route for large Ti-17 die forgings with complex geometry and high fracture toughness requirements. Hand forging trials with four different thermomechanical processing routes resulting in a lamellar microstructure have been performed and their strength and fracture toughness properties were studied. In addition, one die forging using a promising process route was manufactured and strength and fracture toughness were compared with values typically achieved for Ti6-4.